Analysis of The Performance Solar Desalination Proses With Spray in The Evapoarator Room - Munawar Alfansury Airegar; Wawan Septiawan Damanaik; Sudirman Lubis; Jandri Fan HT Saragi; Arya Rudi Nasution (Fakultas Teknik UMSU, 2022)
The shortage of clean water sources on the earth's surface is a concern for the future. Utilization of solar thermal energy is something that can be done to get an environmentally friendly system. Desalination process is a method to produce clean water that is cheap and safe. With the experimental method, the desalination process is tested by providing a working system that considers the materials used and the addition of supporting work tools. The evaporator cover is designed to be made of clear glass with a thickness of 3 mm and an area of 1 m2 with a double slope model with an angle of 15o to the east and west, and was tested for 8 days. The result of the radiation heat transfer coefficient is that the highest convection coefficient outside the evaporator is 97.94 W/m2 on the fourth day and the value of the radiation heat transfer coefficient from the glass surface to the environment is 83.85 W/m2 on the second day. Meanwhile, the highest evaporative heat transfer coefficient was 20.30 W/m2 on day four, the highest convection heat transfer coefficient was 3.08 W/m2 on the first day, and the highest radiation heat transfer coefficient was 13.18 W/m2